Augmentation and displacement effects of multiplayer social network games: Examining the roles of social interactions and co-players' identities. (June 2021) - Qin, Yuren; Cho, Hichang; Zhang, Lianshan
Highlights: Players engaged in different interaction modes in multiplayer social network games. The effects of gameplay on loneliness are mediated by different interaction modes. Co-players' identity (friend vs. guild members) matters in the mediation effects. The augmentation and displacement effects possibly coincide. Abstract: The academic debate on whether gameplay has a positive or negative effect on players' psychosocial well-being has yet to cease. To resolve this debate, this study focuses on multiplayer social network games (MSNGs), the affordances of which may lead to the coexistence of augmentation and displacement effects. To unpack the conditions under which gameplay has a positive or negative relationship with psychological well-being, this study distinguishes between co-player interaction modes (in-game social interactions vs. social media interactions) and between co-players' identity types (offline friends/acquaintances vs. guild members). An online survey was conducted with 300 gamers in China. The results revealed that more in-game interaction with co-players was positively associated with players' loneliness, whereas more social media interaction with co-players was negatively related to players' loneliness, regardless of the co-players' identities. However, players who played with offline friends/acquaintances did engage in more social interactions than those who played with guild members, especially social media interactions. Moreover, the effect of playing with friends/acquaintances or guild members on players' loneliness was fully mediated by in-game social interactions and social media interactions. That is, the psychosocial influence of gameplay heavily depends on the exact social interactions that players are involved in rather than on general time spent in games, and the augmentation and displacement effects possibly coincide within one game.